A Cognitive-Pragmatic Analysis of Schematic Structure of Selected Husseini Sermons with Reference to Ahmed Al-Waeli’s Sermons - Basim Jubair Kadhim (Randwick International of Education and Linguistics Science Journal, 2022)
This research is concerned with the schematization of certain subschemata within the Husseini sermons as a religious genre that emphasizes good religious, social, and political attitudes. Based on Stockwell’s 2002 model of the schematic structure, several Al-Waeli’s sermons on the Husseini cause have been analyzed. The analysis has yielded several essential conclusions on the level of the cognitive conceptualization and the level of theme. Regarding the conceptualization, the employment of the objectives of the Husseini cause as a revolution against tyranny and persecution to address the public has triggered different scripts and frames within the major schemata of the Husseini discourse. As for the thematic conclusion, the Husseini discourse is a positive genre including good values and concepts that are adopted by Human rights such as freedom, love, peaceful coexistence, social equality, economic solutions, and other relevant issues. This research has a positive impact on humans’ cognitive behavior.